Development of a monoclonal antibody to detect αs1-casein in the milk of healthy and mastitis-affected goats - Ming PANG; Xiong GUAN; Chen-Xiang ZUO; Ming-Jie LIU; Saad REHMAN; Qin-Lei FAN; Ping LU; De-Kun CHEN; Wen-Tao MA (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2019)
This study aimed to evaluate the expression level of caseins during mastitis of goats. Whole goat caseins were used as primary antigens for mouse immunization. A monoclonal antibody (mAb) named 5B with high specificity to goat αs1-casein was developed. Further results showed that mAb 5B can successfully be applied to western blot and ELISA. In addition, immunofluorescence analysis using this mAb showed increased milk αs1-casein level in mastitis-affected goats. In conclusion, this study has established an effective tool to evaluate the expression level of αs1-casein during mastitis development.